Degradation analysis of 28 year field exposed mono-c-Si photovoltaic modules of a direct coupled solar water pumping system in western Himalayan region of India. (June 2015) - Chandel, S.S.; Nagaraju Naik, M.; Sharma, Vikrant; Chandel, Rahul
Abstract: It is important to understand photovoltaic (PV) module degradation for the design of PV systems. In the present study results of degradation in mono-crystalline-silicon PV generator of a solar water pump after 28 years of outdoor exposure at a western Himalayan location in the Indian state of Himachal Pradesh, are presented. The main objective is to study the impact of PV degradation on solar pump performance, reliability and life-expectancy under field conditions. Main defects observed in PV modules are encapsulant discolouration, delamination, oxidation of front grid fingers and anti-reflective coating, glass breakage and bubbles in back sheet. Hot spots are identified using thermal imaging and degradation is quantified by measuring PV parameters under indoor and outdoor conditions. Sun simulator is used to test degraded modules under standard testing conditions. Average power degradation of PV generator is found to increase 1.4% per year which is reasonable considering materials and technology used about three decades ago. The open circuit voltage is found to show an average increase of 2.8% requiring further experimental investigations. The study has relevance in improving the performance and life-expectancy of PV based systems beyond the warranty period of 25 years by replacing most degraded modules. Follow up research areas are also identified. Highlights: Mono-c-Si PV generator degradation of a solar water pump after 28 years of outdoor exposure is studied. Average power degradation in PV modules is found to increase 1.4% per year. Open circuit voltage is found to show an average increase of 2.8% which requires further research. Study has relevance in improving the performance and life-expectancy of PV systems beyond warranty period.